Usefulness of Spoligotyping in Molecular Epidemiology of Mycobacterium bovis-Related Infections in South America - Zumárraga, Martín J. (American Society for Microbiology, 1999)
Two hundred twenty-four Mycobacterium bovis isolates, mainly from South American countries, were typed by spoligotyping, and 41 different spoligotypes were identified. A total of 202 M. bovis isolates (90%) were grouped into 19 different clusters. The largest cluster contained 96 isolates (42.8%) on the basis of the most frequently observed spoligotype, spoligotype 34. Nineteen M. bovis isolates from humans in Argentina had spoligotypes and polymorphic GC-rich repetitive sequence (PGRS) types that represented the most common types found among isolates from cattle. All five isolates from Uruguay and three of the six isolates from Paraguay had spoligotypes that were also detected for isolates from Argentina. The spoligotypes of isolates from Brazil, Costa Rica, and Mexico and of some of the isolates from Paraguay could not be found in Argentina. A total of 154 M. bovis isolates were selected in order to compare the discriminative power of spoligotyping and restriction fragment length polymorphism (RFLP) analysis with direct repeat (DR) and PGRS probes. By spoligotyping, 31 different types were found, while AluI-digested DR probe-associated RFLP analysis identified 42 types, and RFLP analysis with the PGRS probe also detected 42 types; these were partly independent of the DR types. By combining the results obtained by spoligotyping and by RFLP analysis with the DR and PGRS probes, 88 different types were obtained. Although the differentiation of M. bovis by spoligotyping was less discriminatory than differentiation by RFLP analysis with the DR and PGRS probes, spoligotyping is easier to perform and its results are easier to interpret. Therefore, for the purpose of typing of M. bovis isolates, spoligotyping could be performed first and the isolates could be grouped into clusters and then analyzed by RFLP analysis with the DR and PGRS probes.